Influence of a normal electric field on surfacewave dynamics - Akimov, Yu.A.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2007)
This paper presents a study of the nonresonant parametric excitation of counter-propagating surface waves by a uniform in space and varying in time electric pump field, perpendicular to a planar plasma-dielectric interface. The criterion of the wave excitation has been derived and analyzed. Expressions for the growth rates in the linear stage of the instability are obtained, and the threshold amplitudes of the external electric field above which the parametric instability can occur are found. The spectrum of the excited waves is analyzed as well.